ADAPTASI ETNIS MELAYU TAMIANG DALAM DINAMIKA SOSIAL DAN CULTURE MASYARAKAT ACEH - Fariadi, Dedi; Fasya, Teuku Kemal; Yunanda, Rizki; Yusmalinda, Yusmalinda (Jurnal Sosiologi Dialektika Sosial, 2023)
This research examines the presence of the Tamiang Malay ethnic group in Aceh, especially in the classification known as host ethnics, which is decreasing in existence amidst the rampant migration of other tribes, especially the Javanese who inhabit plantation areas in Aceh Tamiang. The purpose of this study is to provide a description of the construction of Tamiang Malay culture in the social and cultural dynamics of the Acehnese people. This study uses qualitative methods by collecting observational data, interviews, and documentation studies. The results of the study show that the existence of the Tamiang Malay ethnicity is divided into two Malay community groups that differ in the use of accents in the pronunciation of the language. The Malay tribe who inhabit the upstream part of the Tamiang daily dialect uses the letter "o" and the downstream Tamiang tribe uses the letter "e". The Tamiang Malay ethnicity continues to experience degradation with the large number of immigrants, especially the Javanese ethnicity, resulting in statistical changes. Currently it is estimated that the remaining 40% of the Tamiang Malay Ethnicity, on average they inhabit the coast or the downstream part of Tamiang which are scattered in several sub-districtsPenelitian ini mengkaji tentang tentang keberadaan suku bangsa Melayu Tamiang di Aceh, terutama pada klasifikasi yang disebut sebagai etnis tempatan (host ethnics) yang semakin berkurang keberdaannya di tengah maraknya migrasi suku lain, terutama suku jawa yang mendiami areal perkebunan di Aceh Tamiang. Tujuan dari penelitian adalah memaparkan deskripsi tentang konstruksi budaya Melayu Tamiang dalam dinamika sosial dan culture masyarakat Aceh. Penelitian ini menggunakan metode kualitatif dengan pengumpulan data observasi, wawancara, dan studi dokumentasi. Hasil penelitian menunjukkan bahwa keberadaan etnis Melayu Tamiang terpecah menjadi dua kelompok komunitas masyarakat melayu yang berbeda dalam penggunaan logat dalam pengucapan bahasa. Suku melayu yang mendiami bagian hulu Tamiang dialek sehari-hari menggunakan kalimat dengan huruf o dan suku Tamiang bagian hilir dialeknya menggunakan huruf e. Etnis Melayu Tamiang terus mengalami degradasi dengan banyaknya pendatang, terutama Etnis Jawa, sehingga terjadi perubahan statistik. Saat ini diperkirakan Etnis Melayu Tamiang tersisa 40 %, rata-rata mereka mendiami pesisir atau bagian hilir Tamiang yang tersebar di beberapa kecamatan.